Estimating Benefits of Residential Outdoor Water Conservation: A Step-by-Step Guide - Tatiana Borisova; Laura A. Warner; Weizhe Weng; Jennison Searcy; Anil Kumar Chaudhary; Michael Dukes (EDIS, 2024)
This article was developed to help Extension agents, water-conservation managers, and homeowners estimate the economic benefits of residential outdoor water conservation. It provides guidance for reporting benefits, including lowered utility bills for homeowners, reduced water-delivery costs for utilities, and increased water supply. This publication also offers an example of an impact statement.